2000
DOI: 10.1007/bf03395377
|View full text |Cite
|
Sign up to set email alerts
|

Matching Compound Samples With Unitary Comparisons: Derived Stimulus Relations in Adults and Children

Abstract: This research investigated emergent stimulus relations produced by match-to-sample tasks with compound samples and unitary comparisons. The study was a modified replication of the Markham and Dougher study (1993) and consisted of two experiments. Four adults participated in Experiment 1, and 12 6-to 11-year-old children in Experiment 2. Both experiments . involved the same training and testing sequence: Training of four AB-C relations (A 1 B1-C1, A2B2-C1, A 1 B2-C2, A2B1-C2), followed by C-AB tests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
7
0
6
Order By: Relevance
“…Os pesquisadores dessa área têm chamado de estímulos compostos aqueles que são formados pela sobreposição ou justaposição de outros estímulos, que passam a ser chamados de elementos (Carpentier, Smeets, & Barnes-Holmes, 2000).…”
unclassified
“…Os pesquisadores dessa área têm chamado de estímulos compostos aqueles que são formados pela sobreposição ou justaposição de outros estímulos, que passam a ser chamados de elementos (Carpentier, Smeets, & Barnes-Holmes, 2000).…”
unclassified
“…The AB-X failures could also be related to the experimental sequence. Unlike the study by Carpentier et al (2000), the AB-X training was preceded by matchto-sample training with single-element stimuli (A-B, P-Q). This training sequence may have encouraged the children to attend only to one element of the AB samples (Huguenin, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that, after a history of responding to a particular set of tasks (e.g., simple discriminations) or (unitary) stimuli, mentally young populations frequently do not adapt their performances when more complex tasks (e.g., conditional discriminations) or stimuli (compounds) are introduced (Singh & Solman, 1990;Smeets, Barnes, Schenk, & Darcheville, 1996;Stromer, Mcllvane, Dube, & Mackay, 1993). Specifically, the current research examined whether, following conditional discrimination training with unitary stimuli (A-B and P-O), procedures that had been successfully used for training the AB-X relations and testing transfer (PO-X) in older children and adults in previous research (Carpentier, Smeets, & Barnes-Holmes, 2000;Perez-Gonzalez, 1994, Perez-Gonzalez & Serna, 1993 would be appropriate for preschoolers.…”
mentioning
confidence: 99%
“…During symmetry and transitivity tests these stimuli were decomposed and presented separately, sometimes as samples and sometimes as comparisons, to evaluate the established conditional relations (see also, Carpentier, Smeets, & Barnes-Holmes, 2000;Groskreutz, Karsina, Miguel, & Groskreutz, 2010;Guerrero, Alós, & Moriana, 2015;Maguire, Stromer, Mackay, & Demis, 1994;Pérez-González & Alonso-Álva-rez, 2008;Ribeiro, Miguel, & Goyos, 2015).…”
Section: Stimulus Arrangement In Simple Discriminative Training With mentioning
confidence: 99%